Smoking Negatively Effects Patient-Reported Outcomes Following Arthroscopic Partial Meniscectomy - Nicholas R. Kraus, M.S; Natalie A. Lowenstein, B.S; Kirsten D. Garvey, M.S; Elizabeth G. Matzkin, M.D (Elsevier, 2021)
Purpose: To determine whether active smokers have different patient-reported outcomes relative to nonsmokers for pain, function, and overall health at baseline and 1 or 2 years after an arthroscopic partial meniscectomy. Methods: Patients who underwent arthroscopic partial meniscectomy were identified. Demographic data, including smoking status and patient-reported outcome measures (PROMs), were prospectively collected preoperatively and 3 months, 6 months, 1 year, and 2 years postoperatively. Statistical analysis was performed using the mixed-effects model to compare PROMs preoperatively and 1 or 2 years postoperatively between nonsmokers and active smokers. Results: 509 knees undergoing arthroscopic partial meniscectomy were divided into 2 cohorts: group I, nonsmokers (n = 470) and group II, active smokers (n = 39). There were statistically significant baseline differences in PROMs for nonsmokers versus smokers: visual analog scale (VAS), 5.0 ± 0.4 versus 6.3 ± 0.7, respectively (P = .001); Knee Injury and Osteoarthritis Outcome Score (KOOS) Pain scale, 50.3 ± 3.2 versus 42.5± 5.5 (P = .005); KOOS Symptoms scale, 50.0 ± 3.2 versus 43.6 ± 5.4 (P = .019); and Western Ontario and McMaster Universities Arthritis Index (WOMAC) Pain scale, 57.5 ± 3.4 versus 48.2 ± 6.1 (P = .003). There were also statistically significant differences in nonsmokers versus smokers regarding knee function at baseline shown by the KOOS Activites of Daily Living (ADL) scale: (61.1 ± 3.3 versus 53.5 ± 6.1; P = .015). Baseline mental health, as assessed by the Veterans Rand 12-Item Health Survey (VR-12) Mental Health questionnaire, was also statistically different between nonsmokers (55.4 ± 0.8) and smokers (51.5 ± 3.3; P = .020). Importantly, PROMs for pain and function were lower at all time points for smokers. Conclusion: Patients who were active smokers at the time of partial meniscectomy had significantly worse baseline and postoperative PROMs compared with nonsmokers. Changes from baseline for smokers and nonsmokers were relatively consistent between groups 1 and 2 years postoperatively. Smokers will improve a relatively similar amount as nonsmokers after partial meniscectomy, but their overall PROM scores are lower. Level of Evidence: III, retrospective comparative study.